Facing the Challenges of PBD: An Analysis of the Relationship between Teachers’ Knowledge, Skills, and Attitudes in Batu Pahat District - Ruslan, Nor Aida (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This study aims to analyze the relationship between the knowledge, skills, and attitudes of primary school mathematics teachers in Batu Pahat towards the provision of Mastery Level (TP) in Classroom Assessment (PBD). PBD, as a formative assessment tool, has been introduced in the Malaysian education system to assess student development continuously without the pressure of traditional exams. Although PBD brings great potential in improving the quality of education, its implementation faces several challenges. Previous studies have found that confusion about TP evaluation criteria, lack of skills in the implementation of PBD, as well as teachers' negative attitudes, such as the assumption of additional burden, have hindered the effectiveness of this assessment. This study uses a quantitative approach with a questionnaire method involving a stratified random sample consisting of 100 primary school mathematics teachers in Batu Pahat. The questionnaire instrument used measures the level of knowledge, skills, and attitudes of teachers in the context of PBD implementation, as well as involving an analysis of the instrument's reliability. The data obtained was analyzed using statistical techniques such as correlation analysis and multiple regression to determine the strength of the relationship between knowledge, skills, and teachers' attitudes towards the implementation of PBD. The results of the study show that there is a significant relationship between these factors, with knowledge and skills as the main predictors of PBD implementation efficiency. A positive attitude towards PBD also played an important role in the success of this assessment. The findings of this study are expected to provide concrete recommendations to improve the level of understanding and competence of teachers in implementing PBD, thereby improving the learning process of students in Malaysia.
Keywords: Classroom Assessment (PBD); Mastery Level (TP); Teacher Knowledge; Teacher Skills; Teacher Attitude; Mathematics Education; Elementary School